Labour Administration Reforms in China - Casale, Giuseppe (International Labour Organization, 2013)
This timely volume provides a unique and comprehensive overview of the evolution of labour administration in China and details the recent reforms of its legislation and institutions. It gives a clear explanation of the principles and practical working of labour administrations in workplace-specific issue such as occupational safety and health, labour relations, and working conditions, as well as in the public employment services, labour inspection and social security services.